MENINGKATKAN KREATIVITAS BELAJAR BIOLOGI SISWA MELALUI PENERAPAN METODE QUANTUM TEACHING DI MADRASAH ALIYAH NAHDATUL ULAMA BATANG TORU - Herdiani Herdiani; Sahlan Tuah; N Ginting (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2017)
This research was carried outMadrasah Aliyah Nahdatul Ulama Batang Toru years lessons 2015-2016.This type of research is Research Action class (Classroom Action Research) using two cycles of learning. Each cycle starting from the planning, implementation, observation, and reflection. Data collecting techniques used is the test of creativity and observation. Data collection tools used is sheet tests the creativity and student activity observation sheet. Based on the results of the research action class that do obtain test results of creativity learning of biology students ranging from cycle to cycle I II was 1872 with an average of 72.0 with thepercentage of completeness (61.5%) and cycle II 2191 with an average completeness percentage with 84.27 (84.62%). Based on the analysis of data obtained the value of the observation activities of students in cycle I of 66.92% and cycle II of 82.30% observation rating and performance teacher at 67.25% of cycle I and cycle II of 92.9%. In cycle II, has experienced an increase of cycle I and already meets the criteria of research indicators of achievement, then this study finalized on cycle II.Keywords:Creativity, Quantum Teaching method, structure and function of plant tissue.